O serviço social brasileiro e a concepção de intelectual orgânico em Gramsci - Santos, Vivian Pilger (2019)
In this dissertation, the concept of Organic Intellectual in Antonio Gramsci was established as a scientific research theme in the bibliographical production on the Fundamentals of the Brazilian Social Service, proposing to answer the following guiding problem: how historically the Brazilian Social Service appropriated the concept of Organic Intellectual in Gramsci? Thus, it was defined as a general objective: to analyze the appropriation of the conception of Organic Intellectual in Gramsci in the bibliographic production of the Brazilian Social Service. As specific objectives: 1). apprehend the concept of Organic Intellectual in Antonio Gramsci; 2) historically contextualize appropriation of Gramsci's concept of Organic Intellectual in the professional literature of Social Work; 3) learn the debate about Gramsci's conception of Organic Intellectual in the Brazilian Social Work. Therefore, being an exploratory research based on bibliographic research and content analysis, the following works were defined as sample: Faleiros (1985) Iamamoto and Carvalho (1982), Carvalho (1983), Cardoso (1995), Simionato (1995 ) and Abreu (2002), researchers in the field of the intention to break with conservatism and with production between 1980 and 2000. The research affirms the way that this approach of Social Work reconceptualized with the Gramscian work, referring to the intellectual category took place. organic.